A review on heavy metal ions adsorption from water by layered double hydroxide and its composites - Feng, Xiaofang; Long, Runxuan; Wang, Lingling; Liu, Chenchen; Bai, Zhongxiang; Liu, Xiaobo (Separation and purification technology, 2022)
[Display omitted] •We selected to review topics related to the specific application of LDH removal of heavy metals.•Classify and summarize its modification methods, absorption properties, composition, structure, and other aspects.•It is determined that future research needs to reduce environmental impact and economic costs to promote the synthesis and use of LDH.•This system summary will provide helpful guidance for preparing high-efficiency LDHs-based adsorbents and offer critical clues to elucidating the adsorption behavior of heavy metals on LDHs-based materials. Heavy metal pollution is highly toxic and persistent, posing a severe threat to human health, agriculture, and the safe environment. Therefore, there is an urgent need for fast and efficient heavy metal removal technology to deal with emergency response to heavy metal leakage. In recent years, the development of a unique layered double hydroxide material has attracted widespread attention in sewage treatment. Due to these fundamental scientific issues, the general concern about environmental pollution management of LDH-based materials, and the recent significant developments in this field, it is necessary to conduct a thematic review. This article summarizes 474 related articles published since 2005 and outlines functionalized layered double hydroxide (LDH) research status as heavy metal adsorption materials. In addition, there is still a lack of reviews on the adsorption characteristics, interaction mechanism, and application of LDHs-based nanomaterials in heavy metal removal. Here, the primary purpose of this article is to systematically summarize LDHs-based materials and their applications in removing heavy metals from aqueous solutions (Fig. 1). First, we will focus on its preparation and modification methods to understand LDH intuitively. Subsequently, the effects of different environmental conditions on factors such as pH, temperature, and contact time were summarized. Finally, the interaction mechanism between LDHs composites and heavy metals is briefly described, and a quick conclusion is given.